A Study on the Correlation between China’s Stock Market and Economic Growth - KAI, Xin; LIAO, Jiexin (International Journal of Emerging Trends in Social Sciences, 2021)
Stock is an important financial tool, however, due to the imperfect development of China’s stock market, the role of the stock market as an economic barometer is not clear. Meanwhile, there is no consistent conclusion about the correlation between them in the literature. Therefore, based on theoretical models and through empirical methods including regression analysis, Granger causality test, VAR model, this paper tests the relationship between China’s stock market and economic growth from the perspectives of correlation, causality and dynamic relationship, by which we try to make the research more comprehensive and convincing. The results show that these methods are highly consistent: the scale of China’s stock market is large, which makes a great contribution to and has a strong relationship with the economic growth, but the relationship between the liquidity and volatility of the stock market and economic growth is weak. Based on the findings, the products, structure and rules of China’s stock market need to be improved in the future.